The effect of train-the-colonoscopy-trainer course on colonoscopy quality indicators - Hoff, Geir; Botteri, Edoardo; Huppertz-Hauss, Gert; Kvamme, Jan Magnus; Holme, Øyvind; Aabakken, Lars; Dahler, Stein; Medhus, Asle W.; Blomgren, Ingrid; Sandvei, Per; Darre-Næss, Ole; Kjellevold, Øystein; Seip, Birgitte (Endoscopy, 2021)
Background Systematic training in colonoscopy is highly recommended; however, we have limited knowledge of the effects of “training-the-colonoscopy-trainer” (TCT) courses. Using a national quality register on colonoscopy performance, we aimed to evaluate the effects of TCT participation on defined quality indicators.Methods This observational study compared quality indicators (pain, cecal intubation, and polyp detection) between centers participating versus not participating in a TCT course. Nonparticipating centers were assigned a pseudoparticipating year to match their participating counterparts. Results were compared between first year after and the year before TCT (pseudo)participation. Time trends up to 5 years after TCT (pseudo)participation were also compared. Generalized estimating equation models, adjusted for age, sex, and bowel cleansing, were used.Results 11 participating and 11 nonparticipating centers contributed 18 555 and 10 730 colonoscopies, respectively. In participating centers, there was a significant increase in detection of polyps ≥ 5 mm, from 26.4 % to 29.2 % (P = 0.035), and reduction in moderate/severe pain experienced by women, from 38.2 % to 33.6 % (P = 0.043); no significant changes were found in nonparticipating centers. Over 5 years, 20 participating and 18 nonparticipating centers contributed 85 691 and 41 569 colonoscopies, respectively. In participating centers, polyp detection rate increased linearly (P = 0.003), and pain decreased linearly in women (P = 0.004). Nonparticipating centers did not show any significant time trend during the study period. Conclusions Participation in a TCT course improved polyp detection rates and reduced pain experienced by women. These effects were maintained during a 5-year follow-up.